TO THE QUESTION ABOUT INTRODUCTION O F INFORMATION TECHNOLOGIES IN AN EDUCATIONAL PROCESS ON ARTISTICALLY-GRAPHIC FACULTIES (Pedagogy of Higher and Secondary Education, 2022)
The problem of introduction of new information technologies in the process of the special preparation of artiststeachers is examined in the article. On the basis of analysis of possibilities of the known graphic programs the ways of improvement of teaching of computer graphics are traced.